Comparative outcomes of stereotactic body radiotherapy versus radiofrequency ablation in hepatocellular carcinoma within Milan criteria: a systematic review and meta-analysis - Jing, Jianxiong; Zhong, Furui; Zhang, Hao; Luo, Guosong; Du, Zongzhi (Frontiers in Oncology, 2025)
ObjectiveTo systematically compare the clinical efficacy and adverse events between stereotactic body radiation therapy (SBRT) and radiofrequency ablation (RFA) in treating hepatocellular carcinoma (HCC) within the Milan criteria through a meta-analysis.MethodsA comprehensive literature search was conducted in PubMed, Embase, Cochrane Library, Scopus, and Web of Science from database inception to May 1, 2025, for studies comparing SBRT and RFA in HCC patients meeting the Milan criteria. Data were analyzed using RevMan 5.4 software for meta-analysis.ResultsTen studies (9 retrospective and 1 randomized controlled trial) involving 1505 patients were included. Pooled hazard ratios (HRs) for overall survival (OS: HR = 0.98, 95% CI = 0.72–1.32, P = 0.87) and progression-free survival (PFS: HR = 0.84, 95% CI = 0.67–1.06, P = 0.14) demonstrated no significant differences between SBRT and RFA. Subgroup analyses based on tumor diameter, tumor origin type, and study design revealed no significant differences in pooled HRs for OS or PFS. The incidence of adverse events showed no statistical difference between SBRT and RFA (RR = 0.73, 95% CI = 0.53–1.01, P = 0.05).ConclusionSBRT and RFA exhibit comparable efficacy and safety profiles in managing HCC within the Milan criteria.